Higher CSF Levels of NLRP3 Inflammasome Is Associated With Poor Prognosis of Anti-N-methyl-D-Aspartate Receptor Encephalitis - Peng, Yu; Liu, Baozhu; Pei, Shanshan; Zheng, Dong; Wang, Zhanhang; Ji, Teng; Pan, Suyue; Shen, Hai-Ying; Wang, Honghao (Frontiers in Immunology, 2019)
Anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis is accepted as an autoimmune disorder of the central nervous system (CNS). NLR family pyrin domain containing 3 (NLRP3) inflammasome, a potent innate inflammatory mediator, can activate IL-1β and induce the migration of T helper cell into CNS. However, whether NLRP3 inflammasome participates in the pathogenesis of anti-NMDAR encephalitis remains unclear. This study aims to determine the levels of NLRP3 and related cytokines (IL-1β, IL-6 and IL-17) in the cerebrospinal fluid (CSF) of anti-NMDAR encephalitis patients and to assess whether NLRP3 influences the clinical outcomes of this disease. 25 patients with anti-NMDAR encephalitis, 12 viral meningoencephalitis patients and 26 controls with noninflammatory neurological diseases were recruited. CSF NLRP3 inflammasome, IL-1β, IL-6 and IL-17 were measured by enzyme-linked immunosorbent assay. 13 out of the 25 patients were re-examed the concentrations of NLRP3 and cytokines in 6 months later after onset. Our results showed significant increases of CSF NLRP3 inflammasome, IL-1β, IL-6, and IL-17 in anti-NMDAR encephalitis patients. There were positive correlations between CSF NLRP3 inflammasome and cytokines in anti-NMDAR encephalitis patients. There was also a positive correlation between maximum modified Rankin Scale (mRS) scores and CSF NLRP3 inflammasome in anti-NMDAR encephalitis patients. During follow-up, the decrease of mRS was positively correlated with the decrease of CSF NLRP3 inflammasomes. These results suggested that the level of CSF NLRP3 inflammasome could represent the severity of anti-NMDAR encephalitis and the reduction of CSF NLRP3 inflammasome could act as an indicator for the prognosis of this disease.